PELATIHAN PEMBUATAN SABUN PADAT PELATIHAN PEMBUATAN SABUN PADAT ANTIBAKTERI BERBAHAN DASAR DAUN TEMURUI (Murraya koenigii) DI DESA LHOK BANIE, LANGSA BARAT, ACEH - Amna, Ulil; Safrida Sari, Mulia; Amri, Yulida; Fajriani Sukma, Fisca (Fakultas Teknik, Universitas Samudra, 2024)
Skin is the outermost part of the human body, skin will always be exposed to the environment surroundings, starting from exposure to sunlight, temperature, air humidity. Several factors cause dry skin, namely weather, including temperature and humidity, exposure to chemicals and microorganisms, aging, physiological and genetic stress. Efforts that can be made to improve skin conditions caused by microorganisms are the use of antibacterial cosmetics. One plant that can be used as an antibacterial is curry leaves or often known as